2020
DOI: 10.1111/1440-1681.13334
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor‐2 mediates systemic inflammation in gentamicin‐induced rat nephrotoxicity

Abstract: Gentamicin is an aminoglycoside antibiotic commonly administrated to patients with Gram‐negative infections. Gentamicin induced nephrotoxicity by functional and structural impairment. Toll‐like receptors (TLRs) as key mediators in the innate and adaptive immune system response involved in gentamicin‐induced nephrotoxicity. The present study aimed to investigate the gene expression of TLR2 and pro‐inflammatory cytokines in the renal tissues and buffy coat of the whole blood in gentamicin‐treated rats. Twenty ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Previous studies, in agreement with our data, reported the correlation of the inflammatory response to GNT in clinical and animal studies 30,31 . Karimi et al, 32 reported that GNT treatment induced a significant systemic inflammation, which may be linked to the associated increase of pro‐inflammatory chemokines and cytokines like TNF‐α and IL‐1.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies, in agreement with our data, reported the correlation of the inflammatory response to GNT in clinical and animal studies 30,31 . Karimi et al, 32 reported that GNT treatment induced a significant systemic inflammation, which may be linked to the associated increase of pro‐inflammatory chemokines and cytokines like TNF‐α and IL‐1.…”
Section: Discussionsupporting
confidence: 92%
“…First, male gonadal involvement and a subsequent inflammation in testes are possible complications of SARS-CoV-2 (Fan et al, 2020;Ma et al, 2020;Ren et al, 2020;Rival et al, 2006;Xu et al, 2006). Inflammation can lead to excessive production of ROS, and this product can lead to sperm DNA damage (Anifandis et al, 2020;Evenson & Wixon, 2006;Homa et al, 2019;Karimi et al, 2020). Moreover, SARS-CoV-2 infection causes psychological stress, which is a major cause of systemic oxidative stress (Li et al, 2020).…”
Section: Sperm Dfi As a Promising Determiner Of Male Infertilitymentioning
confidence: 99%
“…Recently, it has been reported that apaptosis parameters such as Bax, Bcl-2, Caspase-3, and inflammation pathways such as NF-κB, Nrf-2 and HO-1 are affected [22,23]. The results showed the downregulation of Nrf-2 and HO-1 in the kidney of diabetic rats and revealed that this effect was prevented by PCE treatment by increasing protein expression levels.…”
Section: Discussionmentioning
confidence: 94%